Feedback mechanisms and sensitivities of ocean carbon uptake under global warming - Plattner, G.-K.; Joos, F.; Stocker, T. F.; Marchal, O. (Tellus B: Chemical and Physical Meteorology, 2001)
Global warming simulations are performed with a coupled climate model of reduced complexity to investigate global warming—marine carbon cycle feedbacks. The model is forced by emissions of CO2 and other greenhouse agents from scenarios recently developed by the Intergovernmental Panel on Climate Change and by CO2 stabilization profiles. The uptake of atmospheric CO2 by the ocean is reduced between 7 to 10% by year 2100 compared to simulations without global warming. The reduction is of similar size in the Southern Ocean and in low-latitude regions (32.5°S-32.5°N) until 2100, whereas low-latitude regions dominate on longer time scales. In the North Atlantic the CO2 uptake is enhanced, unless the Atlantic thermohaline circulation completely collapses. At high latitudes, biologically mediated changes enhance ocean CO2 uptake, whereas in low-latitude regions the situation is reversed. Different implementations of the marine biosphere yield a range of 5 to 16% for the total reduction in oceanic CO2 uptake until year 2100. Modeled oceanic O2 inventories are significantly reduced in global warming simulations. This suggests that the terrestrial carbon sink deduced from atmospheric O2/N2 observations is potentially overestimated if the oceanic loss of O2 to the atmosphere is not considered.